Taxonomy, species composition and ecology of seaweed plus preliminary molecular assessment of Caulerpa spp. in Satang and Sampadi Island, Sarawak - Farah Adibah, Esa (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study incorporates morphological and molecular approaches to determine the seaweed species in Satang Besar Island and Sampadi Island, Sarawak. Selected physico-chemical parameters namely temperature, salinity, pH, dissolved oxygen (DO) and turbidity were also measured during the study. Results revealed that there were 17 species of seaweeds (9 families, 11 genera) at Satang Besar Island and 14 species (9 families, 10 genera) at Sampadi Island. There were nine common species at both locations namely Avrainvillea erecta, Cladophoropsis membranacea, Dictyota dichotoma, D. bartayresii, Padina boryana, P. tetrasomatica, Colpomenia sinuosa, Sargassum polycystum and Laurencia majuscula. For both islands, P. tetrasomatica and C. sinuosa were among the most abundant species in terms of percentage cover, frequency and density. Cladophoropsis membranacea and Neomeris van-bosseae were the least representatives species found in Satang Besar Island and Sampadi Island. Bray-Curtis similarity analysis showed that species composition clustered according to habitat preferences. Pearson-correlation showed that salinity moderately correlated with species diversity (r = -0.610; p = 0.000) and evenness (r = -0.603; p = 0.000) in Satang Besar Island, whereas species diversity and species evenness showed a weak negative correlation with turbidity in Sampadi Island (H’: r = -0.428; p = 0.037; J’: r = -0.525; p = 0.008). In this study, approximately 600 bp ITS gene had been successfully amplified from Caulerpa. The data matched with C. serrulata (AY206423.1) and therefore supports the identification using morphological 2 characteristics. Based on phylogenetic tree, Caulerpa showed monophyletic grouping within the division of Chlorophyta.